The Perceived Meanings of Tokopedia Advertisement Video, “Berikan yang Paling Berarti untuk yang Berarti” - L Novelyn (Institute of Research and Community Outreach - Petra Christian University, 2021)
Delivering a message from an advertisement is important to know whether the message that a company wants to transfer is well-delivered or not because the background of audiences may affect them in interpreting the message. Thus, the writer aims to the writer aims to discover how background education affects people to produce information by observing the perceived meanings produced by English Department respondents and Engineering Department respondents. To do so, the writer uses verbal and non-verbal communications Tokopedia